2000
DOI: 10.1002/(sici)1097-4636(200002)49:2<250::aid-jbm14>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Adherence ofStreptococcus mutans to an E-glass fiber-reinforced composite and conventional restorative materials used in prosthetic dentistry

Abstract: The adherence of Streptococcus mutans to E-glass used in fiber-reinforced composites, denture base polymer, and four other restoratives was investigated. The materials were studied with and without a parotid saliva and serum pellicle. Specimens of the studied materials (E-glass, denture base polymer, titanium, cobalt-chromium alloy, gold alloy, and grained feldspar ceramic) were incubated in a suspension of S. mutans, allowing initial adhesion to occur. The degree of bacterial adhesion was studied using scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 33 publications
3
30
0
3
Order By: Relevance
“…[39,41,70]. Additionally, it can occur a binding between and glycoproteins present on mucin which is part of the acquired pellicle [42,68,70,71]. Moreover, these bacteria are able to produce hydrated extracellular polysaccharides (EPS), resulting from sucrose degradation by enzymes known as glycosyltransferase (GTF), as shown in Fig.…”
Section: Presence Of Oral Biofilmsmentioning
confidence: 99%
“…[39,41,70]. Additionally, it can occur a binding between and glycoproteins present on mucin which is part of the acquired pellicle [42,68,70,71]. Moreover, these bacteria are able to produce hydrated extracellular polysaccharides (EPS), resulting from sucrose degradation by enzymes known as glycosyltransferase (GTF), as shown in Fig.…”
Section: Presence Of Oral Biofilmsmentioning
confidence: 99%
“…Thus, the materials interact with the cells through the absorbed protein layer. The composition and structure of this protein layer plays a critical role in determining subsequent cell behavior (2,3,18).…”
Section: Discussionmentioning
confidence: 99%
“…The adherence of bacteria to solid surfaces is thought to involve non-specific processes mediated by physicochemical interactions, such as hydrophobic interaction, electrostatic interaction and hydrodynamic forces (3). Bacterial accumulation in dental biofilms is highly dependent on the characteristics of the material surface.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the present study showed that S. mutans adhesion and viable counts in the biofilm are related, according with Steinberg and Eyal 24 . Several studies have shown that S. mutans has been used in tests on bacterial adhesion because it is the main organism in the process of dental caries and, in dental biofilm formation, in which several bacterial species in the human oral cavity are involved 25,26,27 . The present investigation evaluate the adhesion of S. mutans on smooth and rough surfaces, after immersion in a liquid culture inoculated with S. mutans and a pH 7.0, under this condition both surfaces permitted the bacterial adhesion in a medium proper for bacterial growth.…”
Section: A B Cmentioning
confidence: 99%